Berberis microphylla: a component to protect regeneration of Nothofagus antartica in silvopastoral systems, Argentina - Bustamante, Gimena Noemi; Arena, Miriam E.; Blazina, Ana Paula; Soler, Rosina
Cumulative effects of several anthropic disturbances in native forest makes the regeneration of woody species more difficult. In silvopastoral systems where the impact of herbivory is constant, protective species play a fundamental role to ensure tree seedlings establishment. In Tierra del Fuego, Nothofagus antarctica (ñire) forests were intervened to maximize livestock, but some sectors were burned and overgrazed resulting in a degradation hardly reversible. In these sites, the spiny shrub Berberis microphylla (calafate) grows naturally and vigorously after fire, being less palatable for livestock. The objective of this study was to evaluate the possible nursing effect of calafate shrubs on ñire seedlings in silvopastoral systems of Tierra del Fuego, Argentina. We established a manipulative assay by planting ñire seedlings (2-3 years) under and out of the crown influence of calafate shrubs during spring 2017. After 3 months, we analysed seedling survival and growth: diameter (DAC), height (H), leaf number (LN), leaf size (LL, LW). In addition, in eight different sites we compared isolated advanced regeneration, tree height (HA), shrub height (HC) and browse intensity. The manipulative assay showed that 50% of ñire seedlings survived regardless of the location (under/out of shrub crown). DAC ofthan out of shrub crown (DAC: 0.34mm, H: 2.18cm). Seedlings under shrubs had fewer leaves (LN: 2.87, LL: 4.63, LW: 4.28). Tree-shrub association in comparison to isolated advanced regeneration showed that the browse height was higher (52.2±23.9 cm) and of lower intensity (1.8±3.0 cm) when trees were associated with shrubs compared to isolated trees (34.3±16.8cm and 2.2±2.0 cm, respectively). In addition, ñire trees had higher height in association withshrubs (101.2±54.1 cm) than ñire alone (75.1±39.7 cm). In addition, browsing height was show evidence of some competition for light it is evident that ñire manages to develop under the shrub. It is expected that over time protected plants by shrubs achieve greater survival ...